Concomitant inhibition of PPARγ and mTORC1 induces the differentiation of human monocytes into highly immunogenic dendritic cells - Erra Diaz, Fernando Alberto (2023)
Monocytes can differentiate into macrophages (Mo-Macs) or dendritic cells (Mo-DCs). The cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF) induces the differentiation of monocytes into Mo-Macs, while the combination of GM-CSF/interleukin (IL)-4 is widely used to generate Mo-DCs for clinical applications and to study human DC biology. Here, we report that pharmacological inhibition of the nuclear receptor peroxisome proliferator-activated receptor gamma (PPARγ) in the presence of GM-CSF and the absence of IL-4 induces monocyte differentiation into Mo-DCs. Remarkably, we find that simultaneous inhibition of PPARγ and the nutrient sensor mammalian target of rapamycin complex 1 (mTORC1) induces the differentiation of Mo-DCs with stronger phenotypic stability, superior immunogenicity, and a transcriptional profile characterized by a strong type I interferon (IFN) signature, a lower expression of a large set of tolerogenic genes, and the differential expression of several transcription factors compared with GM-CSF/IL-4 Mo-DCs. Our findings uncover a pathway that tailors Mo-DC differentiation with potential implications in the fields of DC vaccination and cancer immunotherapy.